Paradigma dan Konsep Integrasi Ilmu - M, Marilang; Bahar, Elsa Wildia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This paper aims to find out what the paradigm and concept of knowledge integration are related to high specialization in varios disciplines which causes fragmentation of knowledge. This creates challengs in dealing with the complexity of global problems that cannot be solved with asingle discipline approach. A new paradigm is needed that encourages the ontegration of knowledge to be crucial in facing the dynamics of the times that demand comprehensive and collaborative solutions. The method used for this paper is qualitative research using library study data collection techniques. A paradigm is a person’s way of viewing themselves and their environment which will influence them in thinking , behaving and behaving. Apart from that , paradigm can also mean a set of assumptions, concepts, values and practices that are applied in viewing reality in the same community, especially in intellectual disciplines and integration is a combination of separate parts into one whole , in other words integrated means holistic or comprehensive. While syncretism is an effort to combine general knowledge with religious knowledge to create a new form of science and islam.